Computerized systems for collecting real-time observational data. - Kahng, SungWoo; Iwata, Brian A. (Journal of Applied Behavior Analysis)
Advances in computer technology have led to the development of a number of semiautomated systems for collecting real-time observational data. We conducted a survey of 15 developers of computerized systems and summarized the features of each system. Many of these systems have incorporated laptop or handheld computers as well as bar-code scanners. Most systems used IBM-compatible (DOS or Windows) software, although a few were designed for either the MacOS or some other operating system. The range in prices started from free to more complete systems costing over $1,500. Data analysis programs were included with most programs; however, only about a third of the systems included a program to compute interobserver agreement. Reprinted by permission of the publisher.